2007
DOI: 10.1182/blood-2006-10-052381
|View full text |Cite
|
Sign up to set email alerts
|

Highly homologous T-cell receptor beta sequences support a common target for autoreactive T cells in most patients with paroxysmal nocturnal hemoglobinuria

Abstract: Deficiency of glycosylphosphatidylinositol (GPI)-anchored molecules on blood cells accounts for most features of paroxysmal nocturnal hemoglobinuria (PNH) but not for the expansion of PNH (GPI ؊ ) clone(s).A plausible model is that PNH clones expand by escaping negative selection exerted by autoreactive T cells against normal (GPI ؉ ) hematopoiesis. By a systematic analysis of T-cell receptor beta (TCR-␤) clonotypes of the CD8 ؉ CD57 ؉ T-cell population, frequently deranged in PNH, we show recurrent clonotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 45 publications
(46 reference statements)
4
42
1
Order By: Relevance
“…The underlying pathogenesis directly pointed to undefined immune dysregulation [11]. Lucia Gargiulo et al [12] found highly homologous T-cell receptor beta sequences in most PNH patients which supported the hypothesis that autoreactive T cells selective damage the GPI-negative hematopoiesis. AM Risitano [13] definitely pointed out the large granular lymphocyte-like clonal expansion induced the antigendriven lymphocyte attack on hematopoietic progenitors in PNH.…”
Section: Discussionmentioning
confidence: 71%
“…The underlying pathogenesis directly pointed to undefined immune dysregulation [11]. Lucia Gargiulo et al [12] found highly homologous T-cell receptor beta sequences in most PNH patients which supported the hypothesis that autoreactive T cells selective damage the GPI-negative hematopoiesis. AM Risitano [13] definitely pointed out the large granular lymphocyte-like clonal expansion induced the antigendriven lymphocyte attack on hematopoietic progenitors in PNH.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, mutations other than JAK2 may determine disease phenotype directly or by co-operating with JAK2 mutations. Analysis of the X-chromosome inactivation pattern of clonality in familial cases of myeloproliferative neoplasm 7 has provided support for this hypothesis.…”
Section: Treatment Implicationsmentioning
confidence: 63%
“…In a recent publication, Notaro and colleagues described oligoclonal expansion of cytotoxic T cells, belonging to the same T-cell receptor V-β subfamily; sharing of clonotypes, or the sequence of the antigen-binding region of the T-cell receptor, despite histocompatability antigen differences, was interpreted as the result of a (non-protein) antigen-driven process common to PNH patientspossibly to the GPI anchor itself. 7 In the murine system, we observed marked expansion of specific CD8 cell oligoclones in the marrow and spleen of conditional knock-out animals, reproduced even more dramatically after transplantation; these T cells were neither activated nor associated with active marrow failure and thus appeared to result directly from the induced mutation. …”
Section: The Problem Of Clonal Expansionmentioning
confidence: 91%
“…32 A decline in regulatory T cells might contribute to promote the selective damage to normal GPI + , but not GPI -, hematopoietic cells potentially mediated by an autoimmune attack. 33 However, in our Pig-a deficient mouse model, inadequate effector T-cell activation may account for the lack of autoimmunity and bone marrow failure despite reduced presence of regulatory T cells.…”
Section: Foxp3mentioning
confidence: 99%
“…In humans, oligoclonal expansion of cytotoxic T cells with highly homologous TCR-β molecules suggests an autoimmune process linked to the pathogenesis of PNH. 33 The nature of the target antigens for autoreactive T cells is unknown, but presumably these antigens are expressed on phenotypically normal GPI + hematopoietic stem cells. 33,[39][40][41] We postulate that reduced Tcell activation and decreased response to stimulation-related interferon-γ in GPI -cells would explain why the enlarged pool of clonally-skewed GPI -CD8 T cells did not cause clinical bone marrow failure and PNH in Pig-a deficient mice, even when the proportion of immunosuppressive Treg cells was much reduced.…”
Section: Foxp3mentioning
confidence: 99%